Improving Teacher's Ability in Developing Innovative RPP During The Covid-19 Pandemic Through Academic Supervision Program in SMAN 1 Puloampel Academic Year 2020/2021 - Rohadi, Rohadi (Journal of English Education Studies, 2021)
This School Action Research (PTS) aims to improve the ability of teachers to develop innovative lesson plans through academic supervision (individual scientific and technical supervision models) during the COVID-19 pandemic. This research was conducted in four stages, namely planning, implementation, observation and reflection, and was carried out in two cycles. The research subjects were 4 science teachers and 4 social studies teachers in my school, namely SMAN 1 Puloampel, Serang district, Banten province. The components of the innovative RPP assessment consist of formulating indicators, formulating learning steps (KBM), allocating time, determining learning resources, formulating teaching methods, and formulating assessments while the innovations that are expected in making the RPP are RPPs that can produce, combine, have added value, something new and answers problems and is integrated with Strengthening Character Education (PPK), oriented to HOTS or improving students' higher thinking skills and having 21st-century skills. In the first cycle, the researcher observed an increase in teacher competence in making innovative lesson plans. The results of observations of individual RPP assessments in the first cycle showed an average value of 68.4%. In the second cycle, the teacher's average value increased in making lesson plans, which was 77.6%. While the classical lesson plan completeness assessment from cycle I and cycle II showed a good average value of 73%. This proves that academic supervision can improve the ability of teachers in preparing innovative RPP (Learning Implementation Plans).